Insight into Students’ Perceptions on Synchronous and Asynchronous English Grammar Class - Daswan, Dafirah Dwi Putri; Ariyani, Amra; Sofyan, Ryan Rayhana (ELT Worldwide: Journal of English Language Teaching, 2025)
This study aims to explore students' perceptions on the synchronous and asynchronous English grammar class. The population of this study were English Education students of the class of 2022 at Universitas Negeri Makassar. This study involved 18 participants determined through a purposive sampling technique. The interview was used as the main instrument to collect the data. The results of this study showed that most of the participants viewed synchronous mode negatively because of certain problems such as internet connection problems, ineffective content delivery, inaccurate live assessment, and the rapid unorganized discussion on WhatsApp Groups. Moreover, students tended to view asynchronous mode negatively as well because of the lack of validation and clarification, lack of participation in discussion, challenges in exploring materials leading to miscommunication, procrastination, and slow progress. However, blended synchronous and asynchronous mode was viewed positively since both modes complete one another. The combination of the two modes is expected to solve students’ problems related to learning platforms and learning activities.